Visualization of a giant coronary artery aneurysm by multi-detector computed tomography - Siddique Umer, Ummara; Alam, Shah jehan; Ghaus, Syed; Gul, Seema (Journal of Postgraduate Medical Institute, 2014)
<!--[if gte mso 9]> <![endif]--> The diagnostic criteria, Computed tomography (CT) appearances, and importance of multidetector CT in diagnosis of coronary artery aneurysms is reviewed in this case report. CT coronary angiography was performed using a 128-slice MDCT scanner in an adult male with chest pain and echocardiographic suspicion of a complex lesion in pericardial cavity. CT revealed giant aneurysm of first obtuse marginal (OM 1) branch of left circumflex coronary artery. It was partly thrombosed. There was mild pericardial effusion raising strong suspicion of aneurysmal leak. Results were confirmed on conventional coronary angiography performed later. MDCT can visualize coronary artery aneurysms very precisely and it provides an excellent view of the anatomy of the coronary artery as well as the surrounding tissues. This exact knowledge of the anatomy is crucial for planning a surgical or interventional approach. With the increasing use of multidetector CT (MDCT) to image the coronary arteries, aneurysms will be identified more frequently. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->